2014
DOI: 10.1038/ejcn.2014.188
|View full text |Cite
|
Sign up to set email alerts
|

Severe obesity prevalence in 8- to 9-year-old Italian children: a large population-based study

Abstract: According to the definition used, between 30,000 and 50,000 children aged 8-9 years suffer severe obesity in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
5
30
0
3
Order By: Relevance
“…Only a few countries have examined morbid obesity in children with contrasting results. Studies of Italian children have reported small, but significant, reductions in the prevalence of morbid obesity in recent years, while other countries such as the USA have reported an increase in the prevalence of childhood morbid obesity . The level of morbid obesity has also been shown to vary considerably between countries, including from 1.8% in Australia to 5.6% in the USA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few countries have examined morbid obesity in children with contrasting results. Studies of Italian children have reported small, but significant, reductions in the prevalence of morbid obesity in recent years, while other countries such as the USA have reported an increase in the prevalence of childhood morbid obesity . The level of morbid obesity has also been shown to vary considerably between countries, including from 1.8% in Australia to 5.6% in the USA .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Italian children have reported small, but significant, reductions in the prevalence of morbid obesity in recent years, while other countries such as the USA have reported an increase in the prevalence of childhood morbid obesity. 24,25 The level of morbid obesity has also been shown to vary considerably between countries, including from 1.8% in Australia 11 to 5.6% in the USA. 26 However, study differences, including survey methodology, children's demographic profiles and the definition used for morbid obesity, make intercountry comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of adiposity from childhood to adulthood is much more common for severely obese children [24, 25]. There is a lack of a standard definition of severe obesity in children, both in terminology (severe obesity can be a synonym for morbid or extreme obesity) and in the methodology that defines it, which makes interpreting data about its prevalence difficult [26]. In 2007, the Centers for Disease Control and Prevention (CDC) proposed the age and gender-specific 99th percentile and above of their growth curves as a definition of severe obesity in children [27], while the World Health Organization (WHO) growth reference curves from 2007 enable the extrapolation of a cut-off to define severe obesity [28] at +3 Z -scores relative to the median.…”
Section: Introductionmentioning
confidence: 99%
“…While there are a good number of studies about the prevalence of severe obesity in American children [30-37], the evidence on severe childhood obesity prevalence in Europe is scarce [26, 38-41]. Moreover, no publication comparing data from different European countries has been found.…”
Section: Introductionmentioning
confidence: 99%
“…Esto, junto con un desequilibrio en el balance energético, conduce a un aumento inadecuado del peso corporal (2). Esta condición es una enfermedad multifactorial que plantea un riesgo importante para la salud presente y futura de las generaciones más jóvenes (3). El aumento internacional en el sobrepeso y la obesidad en niños y adolescentes en las últimas tres décadas confirman que es una epidemia global y un importante problema de salud pública que se asocia con complicaciones cardiovasculares, endocrinas y músculo-esqueléticas, además de presentar consecuencias psicosociales (4).…”
Section: Introductionunclassified